The course of lichen sclerosus in pregnancy - Pencko, Kamila; Płonka, Izabela; Kot, Justyna (Nursing Problems / Problemy Pielęgniarstwa, 2023)
Lichen sclerosus is a chronic inflammatory dermatosis of unknown aetiopathogenesis. It is a common disease among women. The highest incidence is observed between the fifth and sixth decade of life and before puberty. Women of reproductive age, including pregnant women, may also be affected, but limited data are available in this population. The purpose of the study was to present the current state of knowledge on the impact of lichen sclerosus on the course of pregnancy and the method of delivery. The literature used in the article comes from the PubMed database. The articles were searched using the keywords: lichen sclerosus and pregnancy. The analysis showed that lichen sclerosus, when properly treated, does not complicate the course of pregnancy and does not affect the delivery method.